PROFILE OF DOMINANT PHYSICAL COMPONENTS AMONG PETANQUE ATHLETES IN SOUTH SUMATRA - Ahmad Hasan Arpani; Bayu Hardiyono; I Bagus Endrawan; Selvi Meliyanti (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aimed to identify and describe the dominant physical components of Petanque athletes in South Sumatra to provide empirical data for targeted training program development. A descriptive quantitative design was employed, involving 30 active Petanque athletes selected through a total sampling technique. Physical components assessed included arm muscle endurance, arm power, hand–eye coordination, static balance, and arm muscle strength. Data were collected through standardized field tests and analyzed using descriptive statistics, normality tests, and homogeneity tests via SPSS version 26.0. Results indicated that the majority of athletes demonstrated good to excellent performance in arm muscle strength, hand–eye coordination, and arm muscle endurance. Specifically, 33.33% of athletes were categorized as excellent, 60% as good, and 6.67% as moderate, with an overall mean score of 28.59 (good category). However, arm power and static balance showed greater variability, with some athletes falling into moderate categories, suggesting areas for improvement. These findings highlight the need for coaches to design specialized training interventions focusing on explosive arm power and balance without neglecting maintenance of already dominant components. The profiling data generated in this study can assist coaches, sports organizations, and policymakers in developing more effective, evidence-based athlete preparation programs for regional and national competitions.